Prioritising CPR Education - Sri Ameera, Abdul Rahim *; Ho, Sweet Lee *; Nitiakaliyani, Balasubramaniam * (Star Media Group Berhad, 2023)
As practising nurses and clinical instructors, we feel the recent schools" (Sept 3; online at bit.ly/cprstar) is very timely. Cardiopulmonary resuscitation (CPR) is an essential and swift technique to address cardiac arrest due to various reasons.